2021
DOI: 10.3390/safety7020044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Self-Reported Agricultural Tasks, Safety Concerns, and Health and Safety Behaviors of Young Adults in U.S. Collegiate Agricultural Programs

Abstract: Young adults enrolled in collegiate agricultural programs are a critical audience for agricultural health and safety training. Understanding the farm tasks that young adults engage in is necessary for tailoring health and safety education. The project analyzed evaluation survey responses from the Gear Up for Ag Health and Safety™ program, including reported agricultural tasks, safety concerns, frequency of discussing health and safety concerns with healthcare providers, safety behaviors, and future career plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Whilst males were significantly more likely to be working with large heavy machinery and driving trucks, females were significantly more likely to be working with livestock (including handling large animals) and using horses for stockwork. These task-based results were similar to those reported among young adults enrolled in the U.S. Gear Up for Ag™ program ( 12 ). Horses are the major cause of injury and death from animals in Australia ( 2 , 3 ), and one area where there is significant differences between the genders.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Whilst males were significantly more likely to be working with large heavy machinery and driving trucks, females were significantly more likely to be working with livestock (including handling large animals) and using horses for stockwork. These task-based results were similar to those reported among young adults enrolled in the U.S. Gear Up for Ag™ program ( 12 ). Horses are the major cause of injury and death from animals in Australia ( 2 , 3 ), and one area where there is significant differences between the genders.…”
Section: Discussionsupporting
confidence: 85%
“…A post-survey rate of 52% is a pleasing result, given the history of low response rates in other agricultural studies. Typically most survey response rates for academic studies of US farmers are ~20% ( 12 , 35 ) and a recent study in Scandinavia found slightly higher results depending on whether email or post ( 36 ). On the post-survey, all students were given the opportunity to provide feedback in the form of a written, qualitative response.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations